Level-set modelling of Laser Beam Melting process applied onto ceramic materials – Comparison with experimental results. (May 2019) - Chen, Q.; Moniz Da Silva Sancho, L.; Guillemot, G.; Gandin, Ch.-A.; Bellet, M.; Bartout, J.-D.; Berger, M.-H.; Colin, C.
Abstract: Laser Beam Melting (LBM) processes benefit from significant progress in recent years. Currently, manufacturing of ceramic parts for applications at high temperature in aeronautical industries can be planned. However, understanding of defect formation is required in order to optimize manufacturing strategy. In this work, level-set modelling is proposed to simulate tracks development during LBM processes. Thermo-mechanical solution is performed in both powder and dense domains. Fluid flow is computed considering the surface tension and Marangoni forces. In addition mechanical resolution is achieved to investigate stress evolution in the rear part of the track. Applications are developed on alumina material. The influence of laser power, scanning velocity and physical properties are investigated and discussed. Validations of the heat source model are proposed by comparisons of melt pool dimensions and shapes with experimental measurements. A coherent evolution of the track morphology is shown when varying process parameters or material properties.